Quantification of Stereochemical Communication in Metal–Organic Assemblies - Castilla, Ana M. (Angew Chem Weinheim Bergstr Ger, 2016)
The derivation and application of a statistical mechanical model to quantify stereochemical communication in metal–organic assemblies is reported. The factors affecting the stereochemical communication within and between the metal stereocenters of the assemblies were experimentally studied by optical spectroscopy and analyzed in terms of a free energy penalty per “incorrect” amine enantiomer incorporated, and a free energy of coupling between stereocenters. These intra‐ and inter‐vertex coupling constants are used to track the degree of stereochemical communication across a range of metal–organic assemblies (employing different ligands, peripheral amines, and metals); temperature‐dependent equilibria between diastereomeric cages are also quantified. The model thus provides a unified understanding of the factors that shape the chirotopic void spaces enclosed by metal–organic container molecules.